PLP1 duplication at the breakpoint regions of an apparently balanced t(X;22) translocation causes Pelizaeus–Merzbacher disease in a girl. (16th March 2012) - Fonseca, ACS; Bonaldi, A; Costa, SS; Freitas, MR; Kok, F; Vianna‐Morgante, AM
<x xml:space="preserve">Abstract</x> Fonseca ACS, Bonaldi A, Costa SS, Freitas MR, Kok F, Vianna‐Morgante AM. PLP1 duplication at the breakpoint regions of an apparently balanced t(X;22) translocation causes Pelizaeus–Merzbacher disease in a girl. PLP1 (proteolipid protein1 gene) mutations cause Pelizaeus–Merzbacher disease (PMD), characterized by hypomyelination of the central nervous system, and affecting almost exclusively males. We report on a girl with classical PMD who carries an apparently balanced translocation t(X;22)(q22;q13). By applying array‐based comparative genomic hybridization (a‐CGH), we detected duplications at 22q13 and Xq22, encompassing 487–546 kb and 543–611 kb, respectively. The additional copies were mapped by fluorescent in situ hybridization to the breakpoint regions, on the derivative X chromosome (22q13 duplicated segment) and on the derivative 22 chromosome (Xq22 duplicated segment). One of the 14 duplicated X‐chromosome genes was PLP1.The normal X chromosome was the inactive one in the majority of peripheral blood leukocytes, a pattern of inactivation that makes cells functionally balanced for the translocated segments. However, a copy of the PLP1 gene on the derivative chromosome 22, in addition to those on the X and der(X) chromosomes, resulted in two active copies of the gene, irrespective of the X‐inactivation pattern, thus causing PMD. This t(X;22) is the first constitutional human apparently balanced translocation with duplications from both involved chromosomes detected at the breakpoint regions.